2009
DOI: 10.2350/08-03-0434.1
|View full text |Cite
|
Sign up to set email alerts
|

ALK Expression in Rhabdomyosarcomas: Correlation with Histologic Subtype and Fusion Status

Abstract: Immunohistochemical staining for anaplastic lymphoma kinase (ALK) has been described in rhabdomyosarcomas (RMS), especially the alveolar subtype. Previous studies have yielded conflicting results regarding the pattern of staining (nuclear versus cytoplasmic), and there has been no correlation with PAX3-7/FKHR fusion status. This study was undertaken to evaluate ALK receptor protein expression in a large series of RMS; to correlate these results with fusion status; and to investigate the possibility of 2p23 amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 38 publications
5
43
2
Order By: Relevance
“…Further, the regulatory sequences of the ALK gene were shown to contain a high-affinity binding site to the PAX3-FOXO1 protein. 38 Although a previous study 20 found no association between FOXO1 rearrangement and ALK immunoreactivity, this discordance may be owing to the difference in the number of cases studied, the ALK staining protocol used, and the molecular method employed to determine the gene rearrangement status.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Further, the regulatory sequences of the ALK gene were shown to contain a high-affinity binding site to the PAX3-FOXO1 protein. 38 Although a previous study 20 found no association between FOXO1 rearrangement and ALK immunoreactivity, this discordance may be owing to the difference in the number of cases studied, the ALK staining protocol used, and the molecular method employed to determine the gene rearrangement status.…”
Section: Discussionmentioning
confidence: 94%
“…Other investigators also reported ALK gene gain/amplification in rhabdomyosarcoma (Table 4), but the number of cases studied was small, and the quantitative definition of gain/amplification was not provided. 19,20,22 Notably, these prior studies either did not use a reference probe 19,22 or separately examined the ALK gene and a reference gene, 20,23 whereas we simultaneously evaluated the ALK and reference genes using a dual-color approach that enabled precise determination of gene copy number at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…130,131 Alveolar rhabdomyosarcoma and neuroblastoma may also be positive in highly sensitive ALK immunohistochemistry. 70,132 There are generally two types of assays used for fluorescence in situ hybridization analyses of fusion genes, i.e., fusion assays and split (break-apart) assays. In fusion assays, the two genes involved are stained in different colors with the fluorescence-labeled probes.…”
Section: Pabpc4-tyk2 Fusion Gene -mentioning
confidence: 99%